THE EFFECTIVENESS OF VIDEO MEDIA AND LEAFLETS IN INCREASING KNOWLEDGE ABOUT ANEMIA FOR PREGNANT WOMEN AT TUNGGAKJATI HEALTH CENTER YEAR 2023 - Nariah, Nariah; Barkah, Asep (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Anemia is a condition where the hemoglobin level, hematocrit and erythrocyte count decrease below normal values. In people suffering from anemia, more often called anemia, the level of red blood cells (hemoglobin/Hb) is below normal values. The incidence of anemia in pregnant women in Indonesia is still quite high, namely 48.9% of the total number of pregnant women. The incidence of anemia in pregnant women at the Tunggakjati Community Health Center has continued to increase in the last three years. Research Objective: To determine the effectiveness of video media and leaflets in increasing knowledge about anemia in pregnant women at the Tunggakjati Community Health Center in 2023. Research Method: The type of research used in this research is quasi-experimental with the design used is a pre and posttest two group design approach. The population in this study was 117 pregnant women at the Tunggakjati Community Health Center. The sample in this study was 54 respondents. Bivariate analysis used the Wilcoxon test. Research Results: Knowledge of pregnant women about anemia in pregnant women after being given video media at the Tunggakjati Community Health Center in 2023 was mostly good, 44 people (81.5%). Most of the knowledge of pregnant women about anemia in pregnant women after being given leaflets at the Tunggakjati Health Center in 2023 was mostly 32 people (59.3%). The average difference in knowledge in the video media group is 8.28, standard deviation 2,023, minimum 4 maximum 12. In the leaflet media group the average is 6.91, standard deviation 2,397, minimum 3 maximum 12 with p-value < α (0.002 < 0.05). Conclusion: It can be concluded that video media is more effective in increasing knowledge about anemia in pregnant women than leaflet media.